Facile green synthesis of ZnO/AC nanocomposites using Pontederia crassipes leaf extract and their photocatalytic properties based on visible light activation - Albo Hay Allah, Mahmood A.; Alshamsi, Hassan A. (Journal of materials science. Materials in electronics, 2023)
Due to the rapid growth of various industrial activities, huge quantities of harmful water contamination are continuously discharged into the water sources causing a series of environmental hazards and problems. Among the most hazardous pollutants of aquatic environment is wastewater containing colored substances that resist biodegradation. Therefore, sufficient and cost-effective techniques is necessary to reduce the pollution risks of the aquatic environment. In the present work, activated carbon (AC) samples were synthesized from Pontederia crassipes leaves and then incorporated with zinc oxide nanoparticles (ZnO NPs) for removing Congo red (CR) dye from aqueous solutions. The morphology, phase structure, surface texture, chemical composition, and optical properties of synthesized nanomaterials were investigated using XRD, FTIR, EDS, FESEM, TEM, RAMAN, and DRS. The results exhibited that inclusion of different AC ratios into ZnO nanostructure had significant effects on structural, morphological, optical, and photodegradation properties. The ZnO/AC(15%) nanocomposite showed the highest photocatalytic performance in terms of photodegradation efficiency as PDE% = 99.17 under optimum conditions ([CR] = 100 ppm, pH = 3, catalyst dose = 1.4 g/L and irradiation time = 180 min). The kinetics study showed that the dye’s photocatalytic degradation reaction was fitted to a pseudo-first-order reaction. The reusability study showed that the ZnO/AC (15%) photocatalyst exhibited a promising photostability, where it retained 82% of its initial photocatalytic activity after successive five cycles. The scavenging study showed that the major active species are responsible for photocatalytic degradation of CR dye are h + and ˙OH. The most significant reduction of photocatalytic activity was caused by the addition of non-ionic surfactants. Results showed that the treatment of CR solution by ZnO/AC (15%)-H 2 O 2 system increased PDE% more than 44% after 60-min irradiation.